STUDY OF ASSESSMENT OF CLINICAL PROFILE AND ETIOLOGY OF PATIENTS OF SEVERE ANEMIA ADMITTED AT TERTIARY CARE CENTER - JOHAR, BEHLOOL; TIWARI, PRATEEK; GUPTA, MANJULA; GUPTA, NIKHIL; DUBE, SIMMI (International Journal of Current Pharmaceutical Research, 2025)
Objective: To study the clinical profile, determine aetiological factors, and assess contributing variables among patients with severe anaemia in a tertiary care setting in Central India. Methods: This observational study was conducted over one year (March 2024–February 2025) at Gandhi Medical College and Associated Hospitals, Bhopal. A total of 150 adult patients with haemoglobin<7 g/dl and undiagnosed anaemia were enrolled. Patients underwent detailed clinical evaluation and comprehensive laboratory investigations. Results: Females comprised 64.7% of the cohort, with a mean age of 53.91±21.62 y. Pallor (100%) and dyspnoea (100%) were universal symptoms. Nutritional anaemia was the predominant cause (83.33%), with iron deficiency anaemia accounting for 60%, followed by vitamin B12 deficiency (20%). Other causes included leukaemia (7.3%), haemoglobinopathies (4.7%), haemolytic anaemia (2.6%), infections (1.3%), and aplastic anaemia (0.7%). mean haemoglobin was 4.47±1.51 g/dl. SGPT levels varied significantly with anaemia severity (p=0.013), while MCV approached significance (p=0.051), indicating hepatic stress and microcytosis in severe cases. Conclusion: Severe anaemia in hospitalized adults is predominantly nutritional in origin, underscoring the need for early detection, nutritional interventions, and public health strategies. Focused community screening and comprehensive management protocols are vital to reduce the anaemia burden and its complications.